DNA synthesis in mammary epithelial cells of Swiss mice during lacation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Croke-Auldist, Danielle E (Massey University, 2003)
Proliferation of extra secretory epithelial cells in mammary glands during lactation could potentially increase milk production, with flow-on benefits such as improved weaning weights of young or increased exports from the dairy cow industry. The primary objective of the research reported in this thesis was to increase proliferation of mammary epithelial cells during lactation so that the mechanisms associated with this phenomenon could be studied. Induction of increased proliferation in mammary glands was attempted by applying challenges to mice which were used as a laboratory model for agriculturally important species such as cows and pigs. The experiments reported in this thesis also included refinement of methodologies developed to study proliferation of secretory cells in mammary glands during lactation. The first was to improve techniques for describing the chemical composition of mammary glands collected during lactation. This was achieved by collecting and analysing the composition of mouse milk at 3 stages of lactation (Chapter 3). While milk protein and milk fat remained constant throughout, the concentration of lactose increased with time. These data were critically important for correcting the weights of mammary glands for milk content. A second investigation was carried out to compare different methods of calculating the milk production of mice (Chapter 3). Three methods were evaluated with the best based on calculating the maintenance energy requirements of the metabolic weight of the litter which was added to the energy required for measured litter growth. The total energy required was then converted to a quantity of milk. The third methodology developed during the course of the work in this thesis was sample preparation for analysis of lactating mammary cells using flow cytometry. One approach to increasing proliferation of mammary epithelial cells during lactation was to increase the suckling intensity of the mice. This challenge was accomplished by either increasing litter size (Chapter 6) or by increasing the ratio of pups per gland by taping over 5 of the 10 glands (Chapter 5), Suckling intensity was increased to 2 pups per gland but the effect was to accelerate mammary gland development in terms of cell number and milk synthesis status. Once a suckling intensity of >1 pup per gland was reached, there was no additive effect on the size of mammary glands or milk production at mid lactation. Mammary glands appeared to have a limit on their size and output which is reached at a suckling intensity of 1 pup per gland. Manipulation of suckling intensity did not produce a suitable model of elevated proliferation of mammary epithelial cells during lactation. Another approach tested was to use exogenous steroids as these had previously caused increased proliferation in mammary glands (Nagasawa and Yanai, 1978; Knight and Peaker, 1982d). The work reported herein showed that the response of mammary glands of mice to administration of steroids was dependent on stage of lactation and the dose (Chapter 4). In mid lactation, mammary glands were unresponsive for the parameters measured but in late lactation, incorporation of [3H] thymidine into DNA increased and milk production decreased in response to higher doses of estrogen. The high estrogen dose did not however yield a suitable model for the study because the elevated incorporation of [3H] thymidine was associated with early involution of mammary glands rather than proliferation leading to a net increase of epithelial cells. The most promising method of analysis came from histological studies of lactating glands of mice labelled for DNA synthesis. Labelling indices of epithelial cells were >1.5 times greater on the edges of glands on D1 of lactation compared to the inner zones of glands. This within mouse variation was much greater than any between mouse variation arising from the suckling intensity and steroid experiments. An attractive feature is that tissues are derived from the same gland and have therefore been exposed to the same factors such as systemic mitogens and nutrition. In addition, the differences in labelling indices were measured in glands of mice suckling litters of 10 pups which is an easily repeatable treatment compared to some of the more complicated treatments tested during the course of this thesis. Dissection of mammary glands into outer and inner zones could provide useful tissue for the study of local factors involved with increased DNA synthesis of epithelial cells during lactation. Histological studies also revealed that following labelling of mammary epithelial cells for DNA synthesis on the day after parturition, the proportion of cells labelled decrease at a constant rate over the next 23 days (Chapter 8). This project has increased the knowledge of manipulations of mouse mammary glands during lactation. It was found that growth of mouse mammary glands during lactation is difficult to increase experimentally and may have limited application as a model system to study regulation of growth of mammary glands during lactation. However, the work completed in this thesis will allow similar work to continue, with a high chance of success of investigating factors involved in mitosis of epithelial cells in lactating mammary glands.
Keywords: Cells; Mammary glands; DNA synthesis; Mice; Fields of Research::270000 Biological Sciences::270600 Physiology::270602 Animal physiology-cell